The role of translation with special reference to Tshivenḓa and English : a case of the Maintenance Act Number 99 of 1998 in South Africa - Mukundamago, Nthuseni Tryphina (University of Limpopo (Turfloop Campus), 2010)
The study examines a variety of problems that are associated with the translation of the Maintenance Act of South Africa (1998) from English into Tshivenḓa. The study also analyses various translation methods and procedures, and attempts to apply them in the translation of the aforementioned Act. Currently, there seems to be a great lack of legal terminology in Tshivenḓa. As a result, officials end up using English when they interact with their clients who are largely illiterate. Therefore, the study focuses on translation strategies that can be invoked in order to solve the problem of lack of terminology in indigenous languages in general and Tshivenḓa in particular. Chapter two gives a review of the literature and theories pertaining to various translation topics such as, definition of translation, types of translation, methods of translation and procedure of translation. Chapter three addresses issues pertaining to the strategies of translation, methods of translation and terminology development or term formation processes in African languages. These aspects are used by the researcher to expand on the aims and objectives of this research study. Chapter four analyses the respondents’ responses with regard to the translation of legal terminology used in the Maintenance Act (no: 99 of 1998) from English into Tshivenḓa language. A questionnaire was used to examine whether respondents would correctly translate legal terminology from English into Tshivenḓa language. Their responses are also discussed here. Chapter five gives a conclusion to this study.
Thesis (M.A. (African languages) --University of Limpopo, 2010
Keywords: Translation; Interpreting; Maintenance Act translation; 421.3976 MUK; Translating and interpreting -- South Africa -- Limpopo; Child support